Roles and factors for development of strong research teams in universities - Hai, Ha Cong; Trong, Nguyen Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
The formation of strong research teams in universities in developed countries has started long years. Practical activities of strong research teams show well effectiveness of scientific-technological activities through right investment and mobilization of resources. The promotion for development of strong research teams was found in focused attentions of many Governments in the world. In Vietnam, during recent years, the guiding lines for development of strong reserch teams to enhance potentials and to accelerate the international integration in science-technology fields were multiply present in important Party and State documents. The paper provides a global view on strong research teams, analysis of roles and factors for development of strong research teams in universities.On this basis, the authors propose some recommendations for Vietnam to intensify development of strong research teams in universities.